Penguatan Literasi Keselamatan Masyarakat pada Perlintasan Sebidang Kereta Api melalui Sharing Session Partisipatif - Agus Nugroho; Sonya Sidjabat; Astri Rumondang Banjarnahor; Irwan Chairuddin; Sinung Tri Nugroho (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
The community service program entitled “Level Crossings, Transportation Mode Safety, and Contemporary Issues” aims to improve public literacy, compliance, and preparedness in managing risks at intersections between railway tracks and roadways. This program was motivated by the high potential for conflict at level crossings due to differences in the operational characteristics of trains and road vehicles, limited safety facilities, the existence of unauthorized crossings, and risky road-user behavior. The activity was implemented through a participatory-educational approach in an online sharing session involving community members, students, academics, road-user communities, transportation practitioners, and relevant stakeholders. The program included material presentation, interactive discussion, experience sharing, problem identification, and formulation of follow-up recommendations. The results indicate improved participant understanding of railway priority, safe crossing behavior, the importance of signs and markings, and the need for social supervision. The activity also encouraged collective awareness, local leadership potential, and collaborative commitment to developing a safety culture. Recommended actions include continuous safety education, mapping of high-risk locations, stronger coordination, improved safety facilities, and better management of hazardous crossings. Thus, this program serves as an initial step toward community empowerment and a safer, more orderly, participatory, and sustainable transportation safety system.